Pengaruh corporate governance terhadap human capital disclosure dengan managerial ownership sebagai variabel moderasi - Kezia Josephine; Vianty Adella Santo; Totti Andrea Leonardo (LPMP Imperium, 2022)
This study examines the effect of corporate governance on human capital disclosure with managerial ownership as a moderating variable. In this study, the components of corporate governance studied consisted of the board of independence (BoI), gender diversity (GD), and the board of activity (BoA). GCG implementation can encourage companies to act in stakeholders' interests, for example, by making disclosures related to human capital. This study examines the effect of the independent variables (BoI, GD, and BoA) on the dependent variable (HCD). This study uses 180 company data samples listed on the IDX and included in the Kompas 100 category for the 2017-2019 period. Hypothesis testing using SPSS statistical software version 25. The results of this study prove that Gender Diversity and the Board of Activity influence Human Capital Disclosure, while the Board of Independence does not affect human capital disclosure. in addition, managerial ownership is not able to influence the relationship between the board of independence, gender diversity, and the board of activity on human capital disclosure.